Association between occupational hearing loss and predicted 10 year cardiovascular risk among middle aged industrial workers - Negin Kassiri; Mohammad Eslami; Yasser Labbafinejad; Motahareh Harati; Saber Mohammadi; Zahra Asadgol (PLoS ONE, 2026)
Purpose Occupational hearing loss is a prevalent occupational disease with potential systemic health implications, including cardiovascular disease (CVD). This cross-sectional study investigated the association between hearing loss and 10-year CVD risk among middle-aged industrial workers in Tehran. Methods A total of 988 workers (83.7% male, mean age 46.8 ± 5.9 years) underwent routine occupational health examinations, including pure-tone audiometry and cardiovascular risk assessment using the WHO/ISH prediction chart. Hearing-loss phenotypes included low-frequency hearing loss (LFHL), high-frequency hearing loss (HFHL), overall hearing loss (HL), and noise-induced hearing loss (NIHL). Ear-specific hearing loss was first assessed separately for the left and right ears; participant-level hearing-loss variables were then defined based on the presence of hearing loss in either ear. The WHO/ISH 10-year CVD risk score was reported descriptively. To avoid conceptual overlap between the composite WHO/ISH score and its component variables, the composite CVD-risk variable was not entered into multivariable logistic regression models. Instead, multivariable logistic regression was used to identify demographic, occupational, and clinical factors associated with each hearing-loss phenotype. Results The prevalence of NIHL was 19.9%. Ear-specific HFHL was observed in 27.2% of left ears and 25.5% of right ears, while LFHL was observed in 17.0% of left ears and 18.0% of right ears. In multivariable logistic regression models, sex and age were the most consistent independent factors associated with hearing loss. Female sex was associated with lower odds of LFHL, HFHL, overall HL, and NIHL compared with male sex. Older age was independently associated with LFHL, HFHL, and overall HL. Smoking was independently associated with HFHL and NIHL, while work experience was independently associated with NIHL. Job type and diabetes were not consistent independent predictors in the adjusted models. The composite WHO/ISH CVD-risk score was not included in the adjusted models to avoid conceptual overlap with its component variables. Conclusion These findings highlight the importance of demographic, behavioral, and occupational factors, particularly sex, age, smoking, and work experience, in occupational hearing loss among middle-aged industrial workers. Although predicted 10-year CVD risk was described in this occupational cohort, the composite WHO/ISH risk score was not included in multivariable models together with its component variables. Hearing conservation programs should integrate noise control, regular audiometric screening, smoking cessation, and cardiovascular risk assessment as complementary components of occupational health surveillance.